2022
DOI: 10.3389/fphar.2021.795884
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Successful Avatrombopag Treatment for Two Cases of Anti-PD-1 Antibody-Induced Acquired Amegakaryocytic Thrombocytopenia

Abstract: Background: Anti-PD-1/PD-L1 immunotherapy has achieved impressive responses in multiple types of malignancies in recent years. However, immune-related adverse events (irAEs) occur and limit their continuous clinical use. Among these irAEs, acquired amegakaryocytic thrombocytopenia (AAT) is rare but often clinically serious, life-threatening and refractory to multiple treatment approaches.Case summary: We reported for the first time the successful treatment of avatrombopag in two cases of anti-PD1 antibody-indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…Such a result might be attributed to the fact that avatrombopag increases only platelet count and does not activate platelets [ 27 ]. Consistent with our results, a recent study reported successful treatment with avatrombopag in two patients bearing urological neoplasms who developed anti-PD1 antibody-induced amegakaryocytic thrombocytopenia and were refractory or intolerant to any other thrombopoietic agents including glucocorticoids, cyclosporine, intravenous immunoglobulin, rh-thrombopoietin, and eltrombopag [ 28 ]. Thus, the present study reproduced the results of clinical trials in the real-world setting, and avatrombopag was considered effective and safe for liver cancer patients with severe thrombocytopenia.…”
Section: Discussionsupporting
confidence: 90%
“…Such a result might be attributed to the fact that avatrombopag increases only platelet count and does not activate platelets [ 27 ]. Consistent with our results, a recent study reported successful treatment with avatrombopag in two patients bearing urological neoplasms who developed anti-PD1 antibody-induced amegakaryocytic thrombocytopenia and were refractory or intolerant to any other thrombopoietic agents including glucocorticoids, cyclosporine, intravenous immunoglobulin, rh-thrombopoietin, and eltrombopag [ 28 ]. Thus, the present study reproduced the results of clinical trials in the real-world setting, and avatrombopag was considered effective and safe for liver cancer patients with severe thrombocytopenia.…”
Section: Discussionsupporting
confidence: 90%
“…It revealed in all cases an absence of megakaryocytes. The cellularity of bone marrow is variable: clear hypoplasia was found in two patients ( 6 , 8 ), moderate hypocellularity (20%–30%) in one patient, and normal one in two others, including our patient ( 8 ). In a surprising way, lymphocyte T-CD8+ infiltration, classically found in BM biopsy of an AAT patient and in other hem-irAEs such as aplastic anemia, is described only in our case ( 3 , 5 , 13 ).…”
Section: Discussionmentioning
confidence: 63%
“…The second case published by Tu et al. also suffered from other cytopenia probably caused by secondary aplastic anemia ( 8 ). BM biopsy is important to exclude blast infiltration, dysplasia, aplastic anemia, or fibrosis.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations